SPÓŁKA EUROPEJSKA - NOWA FORMA WYKONYWANIA DZIAŁALNOŚCI UBEZPIECZENIOWEJ - Jeżowski, Michał (Zeszyty Prawnicze, 2017)
EUROPEAN COMPANY - A NEW FORM OF CONDUCTING INSURANCE ACTIVITY Summary The primary aim of this article is to present legal regulations concerning creation and functioning of the European company as a legal form of conducting insurance activity. A model of a European company has been created to allow a com bination of the economic potentials of existing companies in different M em ber States and their reorganization, which is expected to decrease the costs and improve the management efficiency of insurance companies by eliminating the expensive m ultinational holding structures. In this article the author attempts to present the consequences of introducing a European company in the insurance sector in Poland. A European company gives a possibility of fast development for those insurance companies, the activities o f which cross the borders. The polish insurance companies will face a strong competition but at the same time they will have opportunities to witness and participate in the reforms of the system.